Etika Komunikasi dalam Media Sosial: Tantangan dan Solusinya - Hamama, Syifa (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2024)
The advancement of information and communication technology (ICT) through social media has significantly transformed the way people interact. Social media facilitates communication for personal, social, and professional purposes, with Indonesia ranking 10th in average daily social media usage at 197 minutes per day. However, this convenience also presents challenges related to communication ethics. Ethical communication on social media is crucial to ensure interactions respect social and moral values and do not harm others. Key challenges in applying communication ethics include the spread of misinformation, hate speech, privacy violations, and disregard for social norms. This study aims to analyze the ethical challenges in communication through social media and offer solutions to address them. The research uses a literature review method with an analytical approach to relevant sources. The findings are expected to contribute to creating a more positive and responsible digital communication space.